Global Attractor for a Nonautonomous Inclusion with Discontinuous Right-Hand Side - Kapustyan, O. V.; Kasyanov, P. O. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We consider a nonautonomous inclusion the upper and lower selectors of whose right-hand side are determined by functions with discontinuities of the first kind. We prove that this problem generates a family of multivalued semiprocesses for which there exists a global attractor compact in the phase space.